2008
DOI: 10.2217/17520363.2.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of HIV Immune Reconstitution Inflammatory Syndrome

Abstract: Dysregulation of the immune system drives HIV pathogenesis. As we develop new ways to treat HIV and AIDS, we encounter new clinical ramifications of our treatment on regulatory components of the immune system. HIV-associated Immune Reconstitution Inflammatory Syndrome (IRIS) occurs after initiation of anti-retroviral therapy (ART) with inappropriate and dysbalanced restoration of the immune system resulting in pathologic inflammatory reactions with significant morbidity. IRIS is most commonly associated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 59 publications
0
66
0
4
Order By: Relevance
“…Also critical is the realization that IRIS might be averted if steps are taken to prevent CD4 counts from dropping below 50 cells per microliter and OI is prevented. 5 In those HIV-infected patients on HAART who do develop IRIS when their T-cell antigen-specific immunity is reconstituted following an anergic state, 8 the risk factors for the development of IRIS include the following: 1) the patient being HAART-naïve, which allows a more intense inflammatory response to develop 2,7,8 ; 2) the patient being severely immunocompromised with very low CD4 counts (Ͻ50 cells per cubic millimeter) at the initiation of ART 5,7,11 ; 3) high pre-HAART HIV-1 RNA levels; 4)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also critical is the realization that IRIS might be averted if steps are taken to prevent CD4 counts from dropping below 50 cells per microliter and OI is prevented. 5 In those HIV-infected patients on HAART who do develop IRIS when their T-cell antigen-specific immunity is reconstituted following an anergic state, 8 the risk factors for the development of IRIS include the following: 1) the patient being HAART-naïve, which allows a more intense inflammatory response to develop 2,7,8 ; 2) the patient being severely immunocompromised with very low CD4 counts (Ͻ50 cells per cubic millimeter) at the initiation of ART 5,7,11 ; 3) high pre-HAART HIV-1 RNA levels; 4)…”
mentioning
confidence: 99%
“…falling HIV-1 RNA levels in response to HAART initiation, especially when this fall occurs rapidly and results in significant level reductions and when it takes place within 90 days of the introduction of HAART 2,8,[12][13][14] ; 5) rising CD4 counts after initiation of HAART, especially later in the course of therapy after falling HIV-1 RNA levels have resulted in an initial redistribution of memory CD4 lymphocytes 2,8 ; 6) OI or the patient on treatment for OI when HAART is initiated, especially within a month of the OI diagnosis, because the increased antigenic burden evokes a more robust inflammatory response 2,7,16 ; 7) resumption of HAART after an interruption; 8) younger age; 9) male sex; and 10) genetic factors that alter the clearance of the pathogen (such as with herpesviruses or mycobacteria) or enhance the immune response to it via polymorphisms in cytokine genes. 8,15 While some of these risk factors are still being debated, such as age and sex, 8 and while criteria are still being expanded and further defined 2,17 and the pathogenesis of IRIS remains not wellunderstood (with some investigators suggesting that there may even be different mechanisms for different pathogens), 7,18,28 there is general acceptance that IRIS can be diagnosed in an HIVinfected individual when there is evidence that the patient's immune system is reconstituting (higher CD4 counts and decreasing HIV-1 RNA levels), yet the patient is paradoxically worsening with the development of new symptoms that cannot be explained by drug toxicity, OI, medical noncompliance, or allergic reactions.…”
mentioning
confidence: 99%
“…It is suggested that young patients are at a high risk of developing TB-IRIS, which suggested that TB-IRIS is associated with the patient's age and the duration of HAART treatment. [12][13][14] However, further studies are warranted to explore the exact mechanism. The main symptoms of patients presenting with TB-IRIS was repeated fever (20/20, 100%) in present study, and the incidence was significantly different as compared with co-infected patients who did not develop TB-IRIS (χ 2 = 42.4, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…It is caused by cellular hyperactivity that occurs with rapid numerical and functional recovery of CD4 + T lymphocyte counts, consequently increasing infl ammatory reaction and damage to tissues, which can endanger the patient's life. Although there is no specifi c diagnostic laboratory test for IRIS, predictive risk factors for this disease include high viral load concentration during opportunistic infection, low CD4 + count at the beginning of HAART (i.e., <200 cells/mm 3 ), initiation of HAART shortly after the diagnosis of an opportunistic infection, and a rapid decrease in viral load with treatment 7 .…”
Section: Casementioning
confidence: 99%